Religious Education in the Christian Colleges in India - Pushparajan, A. (Journal of Dharma, 1984)
It is now unanimously accepted that the Church l has made pioneering efforts in the field of modern education in India. The educational institutions run by the Church provide for the Indians with education in every discipline at all levels in all parts of the country. There is no other single group of private institutions which serve the nation with quite the same range and scope, and enjoy the same amount of popularity. It is also well acknowledged that it was the missionary zeal which motivated the Church to undertake her educational endeavours in India. Therefore it is but natural that religious education occupied and still occupies a prominent position in all the Christian educational institutions.